2015
DOI: 10.11138/mltj/2015.5.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma (PRP) treatment of sports-related severe acute hamstring injuries

Abstract: SummaryPurpose: hamstring injury is the most common musculoskeletal disorder and one of the main causes of missed sporting events. Shortening the time to return to play (TTRTP) is a priority for athletes and sports medicine practitioners. Hypothesis: platelet-rich plasma (PRP) injection at the site of severe acute hamstring injury increases the healing rate and shortens the TTRTP. KEY WORDS: platelet-rich plasma (PRP), hamstring injury, return to play, muscle injury, management. What is known about the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 26 publications
0
38
0
8
Order By: Relevance
“…Previous reports show the application of single dose PRP was effective for 3 and 8 weeks after injection in a rat rotator cuff tear model. Conversely, Guillodo et al reported a single dose of PRP was ineffective . Fourth, although C2C12 myoblast cells express proteins necessary for muscle contraction and display the morphology of individual fiber units, there are striking differences between these cells and adult muscle, particularly in their degree of maturation and mode of glucose transport.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show the application of single dose PRP was effective for 3 and 8 weeks after injection in a rat rotator cuff tear model. Conversely, Guillodo et al reported a single dose of PRP was ineffective . Fourth, although C2C12 myoblast cells express proteins necessary for muscle contraction and display the morphology of individual fiber units, there are striking differences between these cells and adult muscle, particularly in their degree of maturation and mode of glucose transport.…”
Section: Discussionmentioning
confidence: 99%
“…Este estudio se efectuó de acuerdo con la declaración PRISMA 2009 (Preferred Reporting Items for Systematic reviews and Meta-Analysis). 8 Se llevó a cabo una revisión sistemática de los artículos publicados sobre el uso de PRP para el tratamiento de lesiones musculares agudas, en PubMed, Medline y la Base de Datos Cochrane de Revisiones Sistemáticas. La búsqueda se realizó en marzo de 2017, al igual que el empadronamiento del estudio utilizando el International Prospective Register of Systematic Reviews (PROSPERO) (registro: 42017065393).…”
Section: Identificación Y Selección De Artículosunclassified
“…Cinco de los siete estudios fueron susceptibles de metanálisis, [8][9][10][11][12] que sumaban 224 pacientes con información sobre el tiempo hasta el retorno al deporte tras la terapia con PRP. El metanálisis demostró una diferencia significativa en el tiempo transcurrido hasta el retorno al deporte con el uso de PRP en comparación con la terapia convencional (-7.80 días; IC95% de -13.48 a -2.12; p = 0,007), heterogeneidad (I 2 = 96%, p <0,00001) (Figura 2).…”
Section: Tiempo Hasta El Retorno Al Deporteunclassified
See 2 more Smart Citations